Efektivitas Terapi Aktivitas Kelompok Model Interpersonal Dan Model Psikodrama Terhadap Perubahan Tingkat Depresi Lansia: Studi Kasus Di Panti Sosial Tresna Werdha Mataram - Yulandasari, Vera (Jurnal Kesehatan Qamarul Huda, 2019)
Depression is one of the psychological problems experienced by the elderly. The environment of residence as one of the factors causing depression caused psychological and physical problems. There are several therapies that can be used to reduce depression in the elderly by interpersonal model activity therapy and psychodrama model group activity therapy. The study uses the Quasy Exsperiment design (Two-Group Pre-Post Test Design). The study population was all elderly who were depressed at the Tresna Werdha Mataram Social Institution and the sampling technique used purposive random sampling. The statistical test used "Mann Whitney Test" to determine the effect of group activity therapy on the level of change in depression. The results showed that there was no significant relationship between the therapy of Interpersonal model group activity with changes in depression levels with p = 0,085, while there was a significant relationship between Psychodrama and changes in depression levels in the elderly with p = 0,005 . So, from both the interpersonal model and psychodrama model group activity therapy, it was found that group activity therapy in the psychodrama model was more effective in changing depression levels in the elderly.